Analysis of energy consumption characteristics and fracture characteristics of moraine grouting solidified body under uniaxial compression - Li, Zheng-rong; Jiang, Ming-gui; Feng, Xing-long; Wang, Shao-yong; Zeng, Qing-tian; Chen, Chong; Liu, Wen-lian; Sun, Wei (Frontiers in Earth Science, 2023)
Glacial movement causes massive accumulation of fine-grained moraine, which often induces slope instability, moraine debris flow, and other geological hazards due to the effects of rain and the ice-snow melting. This study used a modified phosphoric acid-water glass slurry for grouting and curing moraine, and analyzed the influencing law of water glass Baume degree and curing age on energy consumption characteristics as well as the fracture properties of the grout-cured body of moraine using the uniaxial compression test. The results showed that the gel time of phosphoric acid-water glass slurry increased with the increasing addition of phosphoric acid and that it had a mutation phenomenon. The gel time increased linearly with the increasing addition of phosphoric acid before the mutation. Moreover, the compressive strength, pre-peak total energy, pre-peak elastic energy, pre-peak dissipative energy, elastic energy density, dissipative energy density, and pre-peak fracture toughness of the moraine curing body at same curing age increased linearly with the increase of water glass Baume degree by 46%–218%. The compressive strength, pre-peak elastic energy, and pre-peak elastic energy density of the moraine curing body increased with the curing age but grew slowly from 3 days to 7 days and rapidly from 7 days to 14 days. Through regression analysis of the test results, the fracture toughness calculation formula was derived from an energy perspective. These research results have significant implications for the reinforcement of moraine strata grouting and glacial debris flow disaster prevention and control.